Friendly Settlement Agreements under the Inter-American Commission on Human Rights (Period 2010-2020): An analysis of the agreed reparation measures and their degree of compliance - Otero Rodríguez, R. Adelayda (2022)
Friendly Settlement Agreements are a tool through which petitions can be resolved in a non-contentious manner and agreed upon by the parties. There are several types of reparation that are adopted in friendly settlement agreements and these are: medical, psychological and social rehabilitation, measures of satisfaction, economic compensation, as well as measures of non-repetition. This research work is based on the content analysis method; in reference to the description of the data analysis, the reading of 100 cases of friendly settlement from 2010 to 2020 was taken as a basis, the investigative approach is mixed and the design implemented is the case study. The main objective is to analyze the degree of total, partial, substantial partial and pending compliance of the friendly settlement agreements approved by the Inter-AmericanCommission on Human Rights during the period 2010 to 2020. The results of the investigation yielded a significant fact that most the ASA reports are at the partial compliance level, with a high number of 53 cases out of the 100 sampled. To conclude, it is essential to emphasize that the procedure is also an opportunity for States to demonstrate their level of commitment to respect human rights and their duty to ensure their protection and compliance. In addition, it prevents a sociopolitical impact that causes a conviction against States and saves important resources.